Successful control of opioid-refractory cancer pain with methadone in a patient with advanced oral squamous cell carcinoma: A case report. Issue 2 (July 2018) - Sekido, Katsuhisa; Tomihara, Kei; Horikawa, Hideyo; Tachinami, Hidetake; Murakami, Nozomu; Noguchi, Makoto
Abstract: Methadone, a synthetic opioid agonist, is used for pain that is refractory to other opioids. However, limited data on its ability to control pain in patients with oral cancer are available. In this study, we present a case of recurrent oral cancer, in which pain was poorly controlled with high-dose oxycodone but successfully controlled with methadone. A 36-year-old male patient was referred to our hospital for the treatment of recurrent oral cancer. His pain no longer responded to increased dosages of oxycodone, and thus oxycodone was switched to methadone. Ultimately, his pain was successfully controlled with methadone throughout his end-of-life stage.